Nanomaterial coatings applied on stent surfaces. (May 2016) - Bagheri, Mahsa; Mohammadi, Marzieh; Steele, Terry WJ; Ramezani, Mohammad
The advent of percutaneous coronary intervention and intravascular stents has revolutionized the field of interventional cardiology. Nonetheless, in-stent restenosis, inflammation and late-stent thrombosis are the major obstacles with currently available stents. In order to enhance the hemocompatibility of stents, advances in the field of nanotechnology allow novel designs of nanoparticles and biomaterials toward localized drug/gene carriers or stent scaffolds. The current review focuses on promising polymers used in the fabrication of newer generations of stents with a short synopsis on atherosclerosis and current commercialized stents, nanotechnology's impact on stent development and recent advancements in stent biomaterials is discussed in context.